Penerapan teknologi vertikultur sebagai upaya pemberdayaan masyarakat di Kelurahan Sialang Sakti - Zetra Hainul Putra; Arif Rachman Aladiyat; Aprilia Dini; Diwa Maswitra; Fadel Gama Putra; Gabriella Aprissa Sumihar Siregar; Maura Afda Ayurisna; Metta Jayantri Septiana; M. Prana Mega Pratama; Riandy Harvian; Shabillah Julia Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
RW 08 of Sialang Sakti Sub-district, Tenayan Raya District society, majority work as brick craftsmen and mostly carried out by men, while the majority of women work as housewives. In an effort to increase the productivity of housewives and in the establishment of food security, urban farming programs are implemented in this area. The method used is Verticulture. Verticulture method is used because of the weakness of this area which is limited land and poor nutrients in the existing soil. This method also does not need to use a large area of land so that it is easily applied by the community. The planting medium used in this method is used bottles filled with black soil and hung on 0.5 inch ram wire and installed on the walls of residents' houses. The plants grown are bok choy vegetables, green onions and purslane flowers. Mentoring is carried out by the 2021 Kukerta Students by means of lectures and direct practice. This activity has a positive impact on the community and high enthusiasm is also shown by the community. This activity is expected to be an initial movement in the formation of food security and increasing community productivity and increasing people's income. This technology makes it easier for people to obtain vegetables that are cleaner and cheaper.